A hipercorreção na fala de pastores da cidade de Maceió-AL - Silva, Priscila Rufino da (2016)
In this research, we aimed to outline the profile of the members of the community of practice of the Baptist Convention Alagoana from hypercorrection of events in order to evaluate whether social meaning when the emergence of these instances. For the development of this research, we use assumptions of Sociolinguistics variationist (LABOV, 2008[1972]) whose main objective is to demonstrate that the apparent linguistic chaos can be systematized and described, and that the variable uses found in speech may be occurring through influence of linguistic and social factors; whereas adopted theoretical and methodological aspects related to the third wave of sociolinguistic studies proposed by Eckert (2005; 2012) regarding the demarcation of community of practice and the search for social significance associated with linguistic forms. The population chosen to have his speech collected and their modus operandi observed was the community of practice formed by Baptists Pastors of the Baptist Convention Alagoana, stratify the sample according to the extralinguistic factor Time in pastorate into two groups, namely: Pastors with up to 10 years exercising the ministry (T1) and Pastors with more than 10 years (T2) exercising the function in the Baptist Church. Data collection was performed using three different instruments: structured interview (C1), Bible text reading (C2) and explanation of the biblical text (C3). These three collections were selected in order to observe whether the upward formality, motivated by the attention paid to speech (LABOV, 2008[1972]), influences the occurrence of hypercorrection. Simultaneously collected, we used participant observation whose notes have helped us to understand the modus operandi of the chosen community of practice, as well as the concerns and positions of members of the institution, in enabling a global view about the experience of employees and linking these observations to analysis of the phenomenon studied here. After transcribing the data, we analyze occurrences found qualitatively used for this excerpts taken from the structured interview, in order to outline the linguistic correction of imagery that hovers within this community of practice. Next, we describe the cases of hypercorrection more found in our data, in order to highlight the events that can be classified as such in our linguistic variety, as well as present, briefly, an overview of current uses in this community of practice with order to demonstrate the recurring features in the speech of employees with regard to the adoption of a differentiated linguistic variety/prestigious. Finally, we analyze the performance of the two extralinguistic factors, namely: the time the pastorate and the data collection context. Thus, through the results, we showed that the hypercorrection occurrences found in our corpus reflect the imagination of linguistic correctness and use of the prestigious variety required mainly formality of times is more frequent in the speech of Pastors who are starting their ministry and they need to build within this community of practice your persona and/or personal style.